Assessment of Legal Information Needs and Access Problems of Lawyers in Uganda - Tuhumwire, Innocent; Okello-Obura, C. (Library Philosophy and Practice, 2010)
Unresolved legal problems can entrench disadvantage and increase social exclusion unless legal assistance is made available to members of the community (McClelland, 2009). “As a lawyer, and even more so as a local member, I have met a number of people who have been unable to address a small legal problem before it escalates. Often this is because they don't know what to do or where to go", (McClelland, 2009) asserts. Legal information is considered one of the essential ingredients for effective justice to be done in any democratic society. In our day-to-day life, legal issues have become part and partial of our environment. The ever-increasing number of legal cases in the country has enormously led to petitions in court by various people with hope that they will be backed up by lawyers. However, it is worth noting that timely access to the right kind of legal information determines the performance of any legal officer in any judicial process. It is on that basis that this paper examines the legal information seeking behavior of the legal practitioners, the lawyers in Uganda.